2013
DOI: 10.1111/bjd.12417
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol-resistant infantile haemangiomas

Abstract: Summary Backround Propranolol is now widely used to treat severe infantile haemangiomas (IHs). Very few cases of propranolol‐resistant IH (PRIH) are mentioned in the literature. Objectives To describe the characteristics of PRIHs. Methods A national, multicentre, retrospective, observational study was conducted from February 2011 to December 2011. All patients with PRIH evaluated by the members of the Groupe de Recherche Clinique en Dermatologie Pédiatrique from 1 January 2007 to 1 December 2011 were eligible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 31 publications
3
42
0
2
Order By: Relevance
“…The reported success rate from a systematic review and meta-analysis for all published series demonstrated an overall response rate of 97 % among patients treated with propranolol for infantile hemangioma versus a pooled response of 69 % for corticosteroids studies [8]; 0.9 % had propranolol-resistant infantile hemangiomas. Resistance was observed at all ages during early childhood and at any proliferation stage [3].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The reported success rate from a systematic review and meta-analysis for all published series demonstrated an overall response rate of 97 % among patients treated with propranolol for infantile hemangioma versus a pooled response of 69 % for corticosteroids studies [8]; 0.9 % had propranolol-resistant infantile hemangiomas. Resistance was observed at all ages during early childhood and at any proliferation stage [3].…”
Section: Discussionmentioning
confidence: 92%
“…However, Malik et al reported an earlier response in a small group of patients treated with propranolol either monotherapy or combined with corticosteroids compared to steroids monotherapy [13]. Dual therapy with short steroids course could overcome propranolol resistance estimated in a previous study to be of 0.9 % [3].…”
Section: Discussionmentioning
confidence: 93%
“…β-blockers have recently been introduced as a safe and effective treatment for IH [8][9][10][11]. However, their use is not without risk, and not all tumors respond to these drugs [12,13]. These issues have spurred extensive research to clarify the signaling pathways implicated in hemangioma neovascularization in the hope that a greater understanding of its molecular pathogenesis will reveal new strategies to tackle IH.…”
Section: Introductionmentioning
confidence: 99%
“…Propanolol-resistant infantile hemangiomas have been previously described, although rarely, and one study showed an incidence of 0.9% propranolol resistance among 1130 cutaneous hemangiomas [16]. Our experience suggests that the rate of propranolol resistance may be higher in subglottic hemangioma than cutaneous hemangioma, however further studies would be needed to substantiate this finding as well as to determine the mechanism for why subglottic hemangiomas are less responsive.…”
Section: Discussionmentioning
confidence: 58%